Development Strategy of Batik Industrial in Banyumas - Ngaenah, Nur; DWP, Sucihatiningsih; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2020)
Since batik has been acknowledged by the world, the Batik business begins to emerge. Almost every place in Indonesia tries to expose its local heritage as its identity. Banyumas batik has been existing for a long time ago, but its development is not as expected. There are still many problems dealing with it, such us marketing, raw materials, human resources, and financial. This research used a qualitative approach. The data were collected through interviews and questionnaires. The data analysis applied qualitative and SWOT analysis. The findings showed 1) the existence of internal and external factors of Banyumas batik industries, such as production marketing, human resource, raw materials, competition, and regeneration,; 2) based on SWOT analysis, the batik industrial development strategy in Banyumas applied SO (Strength-Opportunity) strategy. It was showed a beneficial situation by using the strength to use the opportunity, such as using modern technology to improve productivity, product quality endurance, develop a wider market network, implement a mentoring program, empower them continuously, use technology to promote social media and innovating the motive and pattern designs to compete fairly.